2002
DOI: 10.1097/00124784-200207000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Linking Birth Certificates with Medicaid Data To Enhance Population Health Assessment

Abstract: This study linked birth certificates with Minnesota Medicaid deliveries in order to identify Medicaid births. This article describes the link between methodology and results. Medicaid claims from 1997 were used to identify women with a delivery code. Identifiers for these women were linked to birth certificate files, with a match rate of 93.2 percent. Women's match status did not differ by maternal age. Women in some border counties matched at much lower rates than the rest of the population. The methodology w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 7 publications
2
11
0
Order By: Relevance
“…However, there was some evidence of systematic differences for the partially linked records that had no infant hospitalization record (‘mothers only’). This group has slightly higher rates of adverse infant outcomes and associated risk factors, consistent with observations in other studies [10,39-41]. Reduced matching of infant records may be related to the association between missing information, social disadvantage and adverse outcomes, or that severely ill infants with prolonged hospitalization may not necessarily be coded as a birth admission.…”
Section: Discussionsupporting
confidence: 85%
“…However, there was some evidence of systematic differences for the partially linked records that had no infant hospitalization record (‘mothers only’). This group has slightly higher rates of adverse infant outcomes and associated risk factors, consistent with observations in other studies [10,39-41]. Reduced matching of infant records may be related to the association between missing information, social disadvantage and adverse outcomes, or that severely ill infants with prolonged hospitalization may not necessarily be coded as a birth admission.…”
Section: Discussionsupporting
confidence: 85%
“…In seven studies, it was found that people in minority groups had lower linkage rates [26,27,35,37-40]. Several studies offered reasons for this finding including subjects in minority groups being treated at facilities with less complete data [38], a lower rate of migrants reporting accidents to the police [40], higher rates of non-consent to data linkage [26] and lower likelihood of having social security numbers recorded [35]. Conversely, in one Australian study, Australian-born mothers had lower linkage rates due to more frequent treatment in private hospitals which lacked data on mothers' full names [20].…”
Section: Resultsmentioning
confidence: 99%
“…As data collection practices and training are likely to vary between sites, 13 of 14 identified studies found a relationship between the quality of linkage at different geographic or hospital sites [25-27,29,33,34,38,40-45] with only one study finding no relationship [21]. Darlymple et al examined the use of a record linkage system to track and identify treatment patterns of patients with psychiatric conditions in Ontario, Canada.…”
Section: Resultsmentioning
confidence: 99%
“…Birth certificates contain demographic and select clinical information that is not available from health plan data, yet will under-ascertain important elements such as early trimester drug exposures that are available from health plan pharmacy data. Methods to link administrative data to birth certificate data have been developed since the early 1990s to facilitate public health research, often on a state-by-state basis [29,30]. Efforts to improve the linkage between data sources have continued [31,32].…”
Section: Future Opportunities To Improve Pregnancy-related Research: mentioning
confidence: 99%